Determinants of Global and Intra-European Imbalances - Gunther Schnabl; Stephan Freitag (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2012)
The paper discusses global current account imbalances in the context of an asymmetric world monetary system and asymmetric current account developments. It identifies the US and Germany as center countries with rising / high current account deficits (US) and surpluses (Germany). These are matched by current account surpluses of countries stabilizing their exchange rates against the dollar (dollar periphery) and current account deficits of countries stabilizing their exchange rate against the euro or members of the euro area (euro periphery). The paper finds that changes of world current account positions are closely linked to the monetary policy decision patterns both in the centers and peripheries. Whereas in the centers current account positions are affected by monetary policies, in the peripheries exchange rate stabilization cum sterilization matters. In specific, monetary expansion in the US as well as exchange rate stabilization and sterilization policies in the dollar periphery are found to have contributed to global imbalances.
urn:nbn:de:gbv:27-20131126-133743-1
Keywords: F31; F32; 330; Global Imbalances; Intra-European Imbalances; Asymmetric Monetary Policies; Foreign Reserve Accumulation; Sterilization; Granger Causality Tests; Panel Regressions; Leistungsbilanz; Außenwirtschaftliches Gleichgewicht; Zentrum-Peripherie-Beziehung; Geldpolitik; Wechselkurspolitik; Welt; EU-Staaten; USA; Deutschland